2012
DOI: 10.1021/jp301879x
|View full text |Cite
|
Sign up to set email alerts
|

Li1.20Mn0.54Co0.13Ni0.13O2 with Different Particle Sizes as Attractive Positive Electrode Materials for Lithium-Ion Batteries: Insights into Their Structure

Abstract: The effect of the synthesis temperature on the chemical composition of "Li 1.20 Mn 0.54 Co 0.13 Ni 0.13 O 2 " was considered using thermogravimetric analyses (TGA) and in situ X-ray diffraction (XRD) during thermal treatment. A continuous and small weight loss is observed above 800 °C because of Li evaporation, and the lamellar phase disappears to the benefit of a spinel-type phase formed above 940 °C. The layered structure is recovered upon cooling under air. "Li 1.20 Mn 0.54 Co 0.13 Ni 0.13 O 2 " materials s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
195
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(223 citation statements)
references
References 30 publications
16
195
2
Order By: Relevance
“…3. When the cut-off voltage is low, e.g., 3.95 V, a reversible redox couple centered at 3.9 V with relatively 6 . 16 A small plateau at 2.5 V on discharge is also noted.…”
Section: ¹1mentioning
confidence: 99%
See 1 more Smart Citation
“…3. When the cut-off voltage is low, e.g., 3.95 V, a reversible redox couple centered at 3.9 V with relatively 6 . 16 A small plateau at 2.5 V on discharge is also noted.…”
Section: ¹1mentioning
confidence: 99%
“…4,5 Recent studies reveal that charge compensation as positive electrode materials is partly achieved by negatively charged oxide ions, instead of classical transition metal ions. 6,7 Our group has recently reported that Li 3 NbO 4 with pentavalent niobium ions and Li 4 MoO 5 with hexavalent molybdenum ions are also used as new host structures for high capacity electrode materials. [8][9][10] In this study, Li 4 MoO 5 -LiFeO 2 binary system is targeted as a new high-capacity electrode material.…”
Section: Introductionmentioning
confidence: 99%
“…19,22,23 However, to obtain such a capacity, these materials must be cycled over a wide potential range of 2.5-4.6 V (vs. Li + /Li), which may be challenging for the current carbonate-based electrolytes. Major issues such as large irreversible capacity (IRC), 19,33,34 voltage fade upon cycling 22,[35][36][37][38][39][40] and poor rate capability 22,41,42 have hindered the application of these materials. * Electrochemical Society Student Member.…”
mentioning
confidence: 99%
“…37 Nevertheless, partial oxygen loss is also inevitable in this system, and in-plane superlattice ordering is lost after charge to the voltage plateau. 6,32,38,39 The oxidation of oxide ions results in partial oxygen loss, and tetravalent manganese ions are in part reduced to the trivalent state on the discharge after charge beyond the voltage plateau. 6,32,34 Moreover, similar to pure Li 2 MnO 3 , the electrode performance of the solid-solution samples highly depends on the particle size.…”
mentioning
confidence: 99%
“…6,32,38,39 The oxidation of oxide ions results in partial oxygen loss, and tetravalent manganese ions are in part reduced to the trivalent state on the discharge after charge beyond the voltage plateau. 6,32,34 Moreover, similar to pure Li 2 MnO 3 , the electrode performance of the solid-solution samples highly depends on the particle size. The extent of oxygen loss vs. hole stabilization (and/or the formation of peroxide ions) is significantly influenced by the particle size.…”
mentioning
confidence: 99%